Le sportif surhomme et sous citoyen : faut-il renoncer à sa liberté individuelle pour faire du sport de compétition ? - Pechillon, E. (Movement & Sport Sciences - Science & Motricité, 2016)
At a time when the implementation of the World Anti-Doping Code 2015 presupposes the harmonization of procedures and the acknowledgement of international standards, there is ground for considering the emergence of a law that has a direct effect on the exercise of individual freedoms. Such a code compels each State to alter their own organizational standards, without necessarily giving up the consistency of their legal system. The transposition into national law of private transnational standards is a source of difficulties in France, where governments have been trying to turn the practice of sports into a public service mission, even if it means creating an exception for sports. It is appropriate to consider the principle and the consequences of the international development of an anti-doping public policy. Is the athlete such a exceptionally gifted individual that he should deserve an exceptional treatment? By taking on the status of an athlete, should an individual relinquish a part of his fundamental rights? An effective war on doping presupposes the implementation of measures that constitute exceptions to ordinary law. The search for performance must not result in treating every athlete as a potential cheat, thus turning him into a subcitizen.